2020
DOI: 10.1038/s41598-020-61319-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety at 6 months of the XEN implant for the management of open angle glaucoma

Abstract: The purpose of this study is to evaluate the efficacy and complications of the XEN implant as a solo procedure or in association with cataract surgery in patients with open angle glaucoma (OAG). All patients who received a XEN implant between June 2017 and June 2018 were included in the study. The primary and secondary outcomes were: the reduction of the intraocular pressure (IOP) at 6 months postoperatively, the decrease of the glaucoma medications 6 months after surgery, the clinical success rate (eyes (%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 22 publications
8
28
0
1
Order By: Relevance
“…A number of studies have examined ab interno XEN Gel Stent implantation in mixed POAG populations and found mean IOP reductions ranging from 28 to 42.1% with postoperative IOPs ranging from 12 to 15 mmHg. 18 , 21 , 22 , 23 , 24 , 37 , 38 , 39 , 40 , 41 Direct comparison of ab interno XEN Gel Stent implantation with trabeculectomy in POAG patients found no difference in the rates of surgical success or reduction in IOP lowering medications. 24 , 39 , 42 , 43 While one study found that trabeculectomy resulted in lower postoperative IOPs, 39 others found no difference.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A number of studies have examined ab interno XEN Gel Stent implantation in mixed POAG populations and found mean IOP reductions ranging from 28 to 42.1% with postoperative IOPs ranging from 12 to 15 mmHg. 18 , 21 , 22 , 23 , 24 , 37 , 38 , 39 , 40 , 41 Direct comparison of ab interno XEN Gel Stent implantation with trabeculectomy in POAG patients found no difference in the rates of surgical success or reduction in IOP lowering medications. 24 , 39 , 42 , 43 While one study found that trabeculectomy resulted in lower postoperative IOPs, 39 others found no difference.…”
Section: Discussionmentioning
confidence: 97%
“…While the XEN Gel Stent has the theoretical potential to achieve IOPs ≤10 mmHg, in practice, post-implantation IOPs are typically in the 12–15 mmHg range in OAG patients using an ab interno approach. 18 , 21 , 22 , 23 , 24 It has been suggested that this discrepancy is due to additional outflow resistance of a suboptimal conjunctival bleb created following ab interno implantation. 25 , 26 In contrast, an ab externo approach offers the opportunity to dissect Tenon's from the episclera and optimize stent positioning, 27 which may allow for better bleb morphologies that can achieve lower IOPs closer to the theoretic limit.…”
Section: Introductionmentioning
confidence: 99%
“…Reported needling rates after XEN microstent implantation differ between study populations. Reported needling rates lie between 22 and 51% during the first year after surgery, and are even reported to be as high as 55% after 3 years of follow-up after XEN microstent implantation 14,18,27,28,[34][35][36][37][38][39] . Length of follow-up, aggressiveness of postsurgical treatment, patient´s preferences and targeted IOP are among the numerous factors influencing needling rates.…”
Section: Discussionmentioning
confidence: 99%
“…13 . The IOP-lowering and medication-sparing efficacy of the XEN microstent has already been demonstrated in different single and multicenter trials 12,[14][15][16] . The aim of this study was to compare the efficacy and safety profile of the XEN microstent with standard TET in a comparable group of POAG cases in a retrospective, monocentric single surgeon setting.…”
mentioning
confidence: 91%
“…Among the complication of glaucoma filtration surgeries, choroidal detachment (CD) is frequently observed. The estimated incidence varies from 3% to 34% and changes accordingly to the surgical technique to the ocular and the demographic characteristics of the patients and the diagnostic technique accuracy [ 1 6 ]. A limited CD can be asymptomatic, resolve spontaneously, and remain undetected if not adequately investigated.…”
Section: Introductionmentioning
confidence: 99%